Durability properties of ternary blended geopolymer concrete under ambient curing - Ramujee, Kolli; Sai Prasad, Karnatakam; Narendra Kumar, B (International Journal of Engineering and Technology, 2018)
The present paper is an attempt to explore the durability properties of ternary blended geopolymer concrete incorporating fly ash, GGBS, wollastonite as appendage of strength parameters. The Large scale production of cement is triggering environmental problems. This has made the researchers to prefer supplementary cementatious material in fabricating concrete. Fly ash [1], GGBS is a waste material produced by industries used as binder material to way towards the waste utilization. Wollastonite, a naturally occurring mineral can be exploited in geopolymer concrete as a partial replacement of fly ash. G40 grade of geopolymer concrete is used in this study and mix design was built accordingly by replacing fly ash by the combinations of wollastonite and GGBS with suitable alkaline solution and Superplasticizer. A constant 50% of fly ash was used for all the mixes and rest 50% with the combinations of 15%,35%; 25%, 25%; 35%,15% of wollastonite and GGBS respectively .In this present experimental work durability tests (mass loss tests) like resistance to sulphateattack, chloride attack; sorptivity, abrasion resistance were explored for plain mix and optimal mix, which was extracted from previous experimental work of compressive strength properties of ternary blended geopolymer concrete.